2018
DOI: 10.1123/jsep.2017-0308
|View full text |Cite
|
Sign up to set email alerts
|

Chunking, Conscious Processing, and EEG During Sequence Acquisition and Performance Pressure: A Comprehensive Test of Reinvestment Theory

Abstract: This study was designed to test the theorized link between reinvestment, motor chunks, and conscious processing, to provide a thorough examination of reinvestment theory. The authors measured electroencephalographic power and connectivity alongside self-reported conscious processing and behavioral indices of chunking in a 2 (group) × 5 (block) mixed-model design. A total of 55 individuals acquired a motor sequence (blocks A1, A2, A3, and A4) by relatively explicit (errorful) or implicit (errorless) paradigms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…The absence of change in T7-Fz connectivity for the task-unrelated self-talk condition inadvertently addresses concerns that previous research utilising this measure may be confounded by between and within participant variability in the use of motivational self-talk (Bellomo, Cooke, & Hardy, 2018). Our findings suggest that changes in T7-Fz connectivity reflect processes that are not directly related to verbal processes, be it task-related or task-unrelated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The absence of change in T7-Fz connectivity for the task-unrelated self-talk condition inadvertently addresses concerns that previous research utilising this measure may be confounded by between and within participant variability in the use of motivational self-talk (Bellomo, Cooke, & Hardy, 2018). Our findings suggest that changes in T7-Fz connectivity reflect processes that are not directly related to verbal processes, be it task-related or task-unrelated.…”
Section: Discussionsupporting
confidence: 53%
“…For example, we found a significant increase in T7-Fz connectivity from t -2 to t +2 for all conditions, suggesting a greater response to the changing demands of our task across time (i.e., movement preparation versus movement execution) than to the between-condition alterations in self-talk and conscious control. It should therefore be reiterated that phase-based connectivity merely measures the phase lag consistency between signals recorded from two sites, with relations drawn to communication pathways being inferred rather than directly assessed (Bellomo et al, 2018;. As such, it also becomes difficult to interpret our finding that T8-Fz connectivity was significantly higher than T7-Fz connectivity for all conditions across the majority of our task phases.…”
Section: Discussionmentioning
confidence: 86%
“…This type of research would benefit from employing brain imaging techniques, such as functional Magnetic Resonance Imaging (fMRI), magnetoencephalography (MEG), and electroencephalography (EEG) to shed light on brain activity during motor skill learning and performance in dual-task conditions. For example, EEG studies have already shown that the power of neural oscillation in the range of high-alpha in the left temporal region (e.g., Kerick et al., 2004 ) and the co-activation (coherence) between the left temporal region and the frontal midline region at the high-alpha frequency bandwidth (e.g., Deeny et al., 2003 ; Zhu et al., 2011 ) reflect the conscious involvement and attentional demands during motor skill learning and performance ( Bellomo et al., 2018 ; Zhu et al., 2011 ). Because the dual-task methodology manipulates the direction of attention and influences the conscious involvement in motor skill learning and performance ( Beilock & Gray, 2012 ), these measures of brain activity could also be sensitive to dual-task conditions.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…So far, studies tested the concept of chunking in sequence learning tasks (e.g., Bellomo et al, 2018; for an overview, see Abrahamse et al, 2013) that, however, differ from learning complex motor skills with different types of instruction. Recently, Van Duijn et al (2019a) investigated the effect of different types of instruction on cognitive processes by using electroencephalography (EEG).…”
Section: Introductionmentioning
confidence: 99%